Synthesis and reactivities of triphenyl acetamide analogs for potential nonlinear optical material uses - Israr, Hira; Rasool, Nasir; Rizwan, Komal; Hashmi, Muhammad Ali; Mahmood, Tariq; Rashid, Umer; Hussein, Mohd Zobir; Akhtar, Muhammad Nadeem (MDPI, 2019)
We have synthesized aniline based amides (3a–h) via palladium catalyzed Suzuki cross coupling of N-(2,5-dibromophenyl) acetamide with different arylboronic acids in moderate to good yields. A variety of functional groups were well tolerated in reaction conditions. For exploring the possible applications as optoelectronic devices, the nonlinear optical (NLO) properties of all synthesized derivatives (3a–h) were investigated with the help of density functional theory (DFT) methods. The frontier molecular orbitals analysis and reactivity descriptors were investigated for exploring the reactivities.